Partisipasi Masyarakat dalam Konservasi Pesisir Melalui Penanaman Mangrove di Kampung Melayu, Kota Batam - Hanif Hafizodin; Dwi Tari Yufeni; Putri Ulfa Kamalia; Isra Kamelia; Mohammad Aras (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Mangrove ecosystems are important coastal ecosystems that provide ecological, social, and economic benefits to coastal communities. The sustainability of mangrove ecosystems depends not only on planting activities but also on community participation in conservation, maintenance, monitoring, and environmental management. This study aims to describe community participation in coastal conservation through mangrove planting activities in Kampung Melayu, Batam City. The study used a descriptive qualitative approach supported by descriptive quantitative data. Data were collected through observation, interviews, documentation, and activity records. The activity involved 15 community participants and resulted in the planting of 50 mangrove seedlings. The activities included mangrove planting, environmental clean-up, and providing information on post-planting mangrove maintenance. The results indicate that community participation was demonstrated through direct involvement in mangrove planting and environmental clean-up activities. The activity also provided an opportunity to increase community awareness regarding the importance of mangrove ecosystems and the need for continued maintenance. However, the success of mangrove restoration cannot be assessed solely based on the number of seedlings planted. Long-term restoration requires continuous maintenance, monitoring of seedling survival, appropriate site selection, environmental education, institutional support, and collaboration among local communities, universities, government institutions, and other stakeholders. Therefore, participatory mangrove planting should be developed as a continuous conservation program that involves communities throughout the planning, implementation, maintenance, monitoring, and evaluation stages.